2011
DOI: 10.2298/tsci11s1069w
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound thermal process on extracting flavor and caffeine of coffee

Abstract: In this research, our focus is the use of ultrasound thermal process to extract flavor and caffeine from coffee. The different operating conditions for extraction experiments are executed and the results are also compared. The results show that coffee flavor is not enhanced with the increase of temperature because the volatile degree of coffee flavor components is quick and easy to be reached at high temperatures. From the experimental results, it can be found that using low vibration frequency is better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…The energy burst from UAE equipment causes thermal heating that reduces extraction time. Wang et al [ 117 ] have found that quantity of caffeine extracted from coffee reached saturation in only 15 s and augmented positively with increase in temperature at an operating frequency of 28 kHz. UAE was successfully applied to the determination of TRG in coffee powder and instant coffee with excellent recoveries [ 118 ].…”
Section: Extraction Methods For Bioactive Micronutrients Of Coffeementioning
confidence: 99%
“…The energy burst from UAE equipment causes thermal heating that reduces extraction time. Wang et al [ 117 ] have found that quantity of caffeine extracted from coffee reached saturation in only 15 s and augmented positively with increase in temperature at an operating frequency of 28 kHz. UAE was successfully applied to the determination of TRG in coffee powder and instant coffee with excellent recoveries [ 118 ].…”
Section: Extraction Methods For Bioactive Micronutrients Of Coffeementioning
confidence: 99%
“…In this research we tried to produce a saffron extract using different solvents and to improve saffron quality factors in the extract in comparison to the control sample. The selection of the most appropriate solvent for extracting the compounds of interest from a sample is an essential step for developing any extraction method (Wang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Jaringan rumput laut K. alvarezii varietas cokelat dengan bentuk sel yang sehat menunjukkan bagian korteks yang teratur dan tidak renggang (antar dinding sel rapat) (Maulani et al 2017). Namun banyaknya rongga mikro yang dihasilkan oleh ultrasonik mampu membantu memecahkan dinding sel Shirsath et al 2012), sehingga peningkatan kecepatan kontak antara bahan dan pelarut membantu peningkatan penetrasi cairan menuju dinding sel dan melepas komponen sel (Wang et al 2011).…”
Section: Histologi Jaringan K Alvareziiunclassified
“…Figure 4 A) Extraction of phycoerythrin and maximum absorbance spectrum of phycoerythrin pigment before precipitation; B) extraction of phycoerythrin and maximum absorbance spectrum of phycoerythrin pigment after precipitation using aquadest pH 7 with extraction time (W 1 ) 35 minutes, (W 2 ) 45 minutes, (W 3 ) 55 minutes mikro sehingga akan mempersingkat waktu proses dan mengoptimalkan penggunaan pelarut (Shirsath et al 2012). Peningkatan kecepatan kontak antara ekstrak dan solven menyebabkan peningkatan penetrasi cairan menuju dinding sel dan melepas komponen sel (Wang et al 2011). Kelebihan metode UAE (Ultrasonic Assisted Extraction) adalah dapat mengeluarkan ekstrak dari matriks tanpa merusak merusak struktur jaringan (Babaei et al 2006).…”
Section: Ekstraksi Pigmen Fikoeritrin Dengan Lama Waktu Berbeda Kenampakan Dan Spektrum Absorbansi Fikoeritrinunclassified